ANALISIS BIAYA PEMBIBITAN AKASIA (ACACIA CRASSICARPA) PADA HUTAN TANAMAN INDUSTRI (STUDI KASUS DI PT. SINAR SAN JAYA, KECAMATAN KUALA KAMPAR, KABUPATEN PELALAWAN) - Aluisius Bastian Poltak Sinaga; Emy Sadjati; Muhammad Ikhwan (Indonesian Journal of Agricultural Economics, 2017)
The objectives of this research were: (1) To find out the production cost of Acacia Crassicarpa nursery in Industrial Plantation Forest in Serapung Island; and (2) Analyzing the feasibility of breeding Acacia Crassicarpa in Industrial Plantation Forests in Serapung Island. The method used was survey method, the implementation of which is observation and interview. The tools and materials used in this study were stationery, cameras, calculators, voice recorders and Microsoft Excel software version 2016. This research was conducted at PT Sinar San Jaya company located in Serapung Island, Kuala Kampar District, Pelalawan Regency Riau. This research was conducted for 3 months from January to March 2017. In the procurement of raw materials, a fee was of IDR 651,242,000. The costs required, consisting of fixed costs and variable costs. Fixed costs consist of salaries of permanent workers, costs of fertilizers and chemicals, fuel costs, oil costs and procurement costs of nursery equipment totaling IDR 2,007,756,932, while for non-fixed costs, the salaries of non-permanent workers, the cost of fertilizers and chemicals, the cost of procuring nursery equipment with a total value of IDR 187,249,790. The total production cost is IDR 2,195,006,722. While the total income is IDR 3,965,371,640 from the production of seedlings totaling 4,088,012 stems at a price of IDR 970, - per stem, with a net profit of IDR 1,770,364,918. Break Event Point value (BEP) or break-even point (income equal to cost) is IDR 2,478,712,261, -. Whereas this business feasibility is shown by the Benefit Cost Ratio (BCR) value of 1.40, which means that this business is feasible.